2012
DOI: 10.1007/s10439-012-0590-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbachol-Induced Volume Adaptation in Mouse Bladder and Length Adaptation via Rhythmic Contraction in Rabbit Detrusor

Abstract: The length-tension (L-T) relationships in rabbit detrusor smooth muscle (DSM) are similar to those in vascular and airway smooth muscles and exhibit short-term length adaptation characterized by L-T curves that shift along the length axis as a function of activation and strain history. In contrast to skeletal muscle, the length-active tension (L-T(a)) curve for rabbit DSM strips does not have a unique peak tension value with a single ascending and descending limb. Instead, DSM can exhibit multiple ascending an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…However, with repeated contractions, T a is recovered and approaches the original T a seen at that length. This active process of length adaptation, previously identified by the authors in rDSM, has also been demonstrated in respiratory and vascular smooth muscles. Furthermore, acute length adaptation has been demonstrated as a shift of the pressure–volume curve in whole mouse bladders, which more closely models human cystometrics …”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, with repeated contractions, T a is recovered and approaches the original T a seen at that length. This active process of length adaptation, previously identified by the authors in rDSM, has also been demonstrated in respiratory and vascular smooth muscles. Furthermore, acute length adaptation has been demonstrated as a shift of the pressure–volume curve in whole mouse bladders, which more closely models human cystometrics …”
Section: Discussionsupporting
confidence: 68%
“…Total detrusor tension can be analyzed according to its component parts: active tension (T a ) generated by DSM contraction and preload (T p ). T p can be further sub‐divided into passive tension (T pas ) derived from non‐regulatable structural components (i.e., collagen and elastin) and an adjustable preload (T ap ) that has been identified in rabbit DSM (rDSM) and other smooth muscle types . At the molecular level, T ap may result from slowly cycling actomyosin crossbridges .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential physiological roles for LARC in acute length adaptation and adjustable preload have been identified in rabbit DSM [6,21]. Length adaptation and adjustable preload have also been identified in the human detrusor, and the clinical correlate of adjustable preload, dynamic elasticity, has been identified during human urodynamics [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…) and for length adaptation (Speich et al. ). The present data are consistent with a bladder model that includes two contractile systems, one responsible for producing the voiding contraction, and another responsible for SRC, QS‐induced myogenic contraction, generation of APS (Speich et al.…”
Section: Discussionmentioning
confidence: 99%